Factors influencing intention to purchase global brands among Nigerian adults - Anthony, Omaze Afamefuna (2017)
Purchase intention is more complicated and more significant for consumers these days than in the past, due to recent globalization that has led to increased international business activities, with many foreign companies competing with each other. Consumers in developing country like Nigeria have different perceptions toward local and foreign brands, even within the same product category. The main purpose of this study is to examine the factors that influences purchase intention towards global brand among Nigerian adults. This study of Nigerian consumers examines the impact of individual characteristics based on exposure to mass media, materialism, consumer ethnocentrism, and susceptibility to normative influence towards purchase intention of global brands. A total of 318 respondents were involved in this study, and they were selected based on the three local government areas in Lagos state which represent the three senatorial districts in the state. Data were collected using survey through Cluster random sampling technique. Self-administered questionnaire were distributed to the respondents. Findings using ANOVA test showed that there were significant differences for consumer ethnocentrism based on respondents’ background: age, marital status, education and income while no significant difference was found for religion. In addition, significant difference was found for susceptibility to normative influence based on age, but no significant difference based on religion, education level, marital status and income level. For materialism, there were no significant differences based on respondents’ backgrounds such as age, religion, education and income. Significant difference was found based on marital status. However, no significant differences for exposure to mass media and background of the respondents, no significant difference on purchase intention of global brand were discovered based on the backgrounds of the respondents. Moreover, the result of the t-test found no significant differences based on gender for the variables: exposure to mass media, materialism, consumer ethnocentrism, susceptibility to normative influence and purchase intention. The results of correlation were statistical significant for the three independent variables and purchase intention toward global brands, with susceptibility to normative influence having a medium correlation with purchase intention towards global brands, while both exposure to mass media and materialism had a weak relationship. Consumer ethnocentrism had a negative and weaker relationship with purchase intention towards global brands. Result of multiple regression analysis showed that three out of the four independent variables in the model were found to contribute positively and had significant effects on purchase intention towards global brands. Those variables were exposure to mass media, materialism and susceptibility to normative influence, while consumer ethnocentrism was found to contribute negatively. Furthermore, the finding of the result also indicate that susceptibility to normative influence made a significant strongest unique contribution to purchase intention towards global brand, followed by materialism, exposure to mass media and consumer ethnocentrism. This study is significant to consumers, policy makers and local companies. The findings from this study would be valuable contribution in terms of providing strategic alternatives for local products or producers. Thus, it is recommended that local companies need to provide those products that increase the self-esteem of the consumers. They need to regulate the quality of product that can compete with the foreign products by portraying a good advertisement and endorsements of the product by a well know celebrity which can inspire consumers’ intention to purchase local products. While government should also help the local companies by providing the necessary infrastructures that can easily make local product to be available to the consumers and at the same time encourage, and sensitize the consumers the importance of patronize the local brand products.